POTECIAL DE CRESCIMENTO DA CORDIA GLABRATA (MART.) A.D.C EM SUBSTRATO, CITOCININA E GIBERELINA - Caroline Pereira de Jesus , Nielly; da Silva Pires , Valdirene; Fernandes Costa , Brenda; Beatriz Cipriani , Vânia; Gonçalves Mendonça , Cristiane (ANAIS DO ENIC, 2026)
-